Capital structures choice : an investigation in the Singapore context. - Chow, Pei Lin. (2008)
This paper examines the determinants of capital structure of firms listed on the Stock Exchange of Singapore, using data from 1986 to 1995. The study employs variables reflecting differing theoretical arguments on capital structure, namely size, industry and profitability. We found evidence similar to past empirical studies for size and industry but failed to obtain any conclusive results for profitability.